Domestic Accidents in childhood: Identifying potentialities for comprehensive care (Research, Society and Development, 2021)
Domestic accidents in childhood (DAC), although underestimated, are characterized as a relevant health problem in the world, due to their potential severity. According to the Ministry of Health in 2010, there were 11,600 hospitalizations resulting from accidents at home. Nursing professionals have the ability to carry out educational actions with parents and / or guardians and children in order to avoid accidents. Objectives: to identify the main characteristics that surround DAC and what is the role of the nurse in the face of such problem. Methodology: This is an integrative review. The inclusion criteria were: articles with a time frame between 2015 to 2020; in Portuguese, English and Spanish. Databases were used: VHL, SciELO and MEDLINE through PubMed. 13 articles were selected for discussion. Results: 10 national and 3 international studies were identified. As for the type, 10 are original, 2 are for review and 1 is an experience report. The main ADI evidenced were: falls, burn, asphyxiation, cut and intoxication, dog bite and drowning. Discussion: For a better understanding of the theme, the discussion was divided into four categories, namely: Epidemiology of DAC, risk factors, family and children's profile and nursing care in the prevention of DAC. Conclusion: There are several risk factors present in the domestic environment, however, many of these factors can be reduced and even eliminated, based on the awareness of parents and caregivers. The nurse has an essential role in the education of parents and family in the prevention of  DAC.